Association between Fragmented QRS and Left Ventricular Systolic Function in Patients with Erectile Dysfunction - Bektaş, Osman (Acta Cardiol Sin, 2018)
PURPOSE: The aim of this study was to investigate the association between fragmented QRS and left ventricular (LV) systolic function in patients with erectile dysfunction (ED). METHODS: A total of 106 patients with ED and without a history of coronary artery disease (CAD) were compared with 54 age- and gender-matched healthy controls. LV systolic function was evaluated using speckle tracking echocardiography via global longitudinal strain (GLS) and global circumferential strain (GCS). The patients with ED were compared with healthy controls. The study group was further subdivided into fQRS (+) and fQRS (-) groups and compared with each other. RESULTS: The frequency of fQRS was significantly higher in the patients with ED (p = 0.01). The frequency of fQRS was higher in the patients with mild and moderate ED, and significantly higher in those with severe ED (p < 0.001). LV-GLS (%) was 17.46 ± 1.37 and 20.05 ± 1.42 in the fQRS (+) and fQRS (-) groups, respectively (p ≤ 0.001). LV-GCS (%) was 17.33 ± 0.81 and 18.55 ± 0.92 in the fQRS (+) and fQRS (-) groups, respectively (p ≤ 0.001). fQRS and age were independent predictors of LV-GLS. CONCLUSIONS: The frequency of fQRS was higher in the patients with ED even in the absence of overt CAD. In the patients with ED, the fQRS (+) group had significantly lower values of LV-GLS and LV-GCS. These results indicate that presence of fQRS is associated with subclinical LV dysfunction in patients with ED.